(untitled) (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
This research aimed to find out how word card media can improve the students” vocabulary mastery. This research was conducted through classroom action research (CAR). The subject of this research was the students of Seven Grade SMP Negeri 3 Mempawah Hilir, consisted of 30 students. This research used observation and measurement technigue of data collection. The tools of data collection were observation checklist, field note, and vocabulary test. Then, the data analysis in this research used qualitative data and quantitative data. The result of this research showed that the students’ vocabulary mastery was improved from 60 to 81. The students were more active and enthusiastic in following the vocabulary learning process used word card media. So, the researcher suggested to the other teacher who want to teach the students in vocabulary mastery using word card media. word card media is appropriate method used to improve students’ vocabulary mastery.